Variables for Repeated No‐Showing to Clinic Appointments. (2nd September 2014) - Miller, Anya J.; Chae, Esther; Ko, Alvin B.
Abstract : Objectives: Determine the variables that contribute to non‐compliance with showing up to clinic appointments. Patients no‐showing to their appointments represent a significant burden to the health care system by decreasing access to care and lost potential revenue. Identifying patient factors correlated with missed appointments may help characterize why these appointments are missed and identify opportunities to help patients get the care they need. Methods: Retrospective chart review. Patients who did not show up to 3 or more clinic appointments in the otolaryngology department in the Henry Ford system in metro Detroit, Michigan, between July 1, 2011, and June 30, 2012, were analyzed. Controls were patients who had appointments on the same day with the same provider as the no‐show patients. Results: A total of 106 patients were identified who no‐showed to 3 or more clinic appointments. Younger age, black race, and lower income were found to be significant factors for patients not showing up to appointments on multiple variate model. On logistic regression, Medicaid insurance, closer distance from home to appointment, less bus transfers, and less time by bus travel were also found to be significant for no‐showing. Conclusions: Age, race, and income are significant contributors to patient noncompliance with clinic appointments. Paradoxically, proximity to the clinical appointment location is also a significant factor; we hypothesize this may be the result of relative income inequality in the metro Detroit population. Follow‐up studies include analyzing severity of patient complaints and weather as a factor of noncompliance.